A gendered analysis of household energy consumption behavior a comparative study. - Babael, Diana Martinelli C.; Riel, Veronica A.; Yodico, Elaisa Trisha M. (Tacloban City Diana Martinelli C. Babael, Veronica A. Riel, and Elaisa Trisha M. Yodico, 2019)
High levels of energy consumption can result to the exhaustion of fossil energy reserves available in a country, which poses a threat to energy supply. In the Philippines, household consumption accounts for a significant percentage of national energy consumption. For these reasons, the study sought to describe and analyze energy consumption. For these reasons, the study sought to describe and analyze energy consumption behavior at the household level, primarily looking into the effects of gender on energy use and consumption. The attention placed on the gender dimension of energy consumption arose from the lack of sex-aggregated data on domestic energy-related attitudes and practices. The study mainly sought to identify differences between men and women's energy consumption behavior at the household level.
The study was conducted in Brgy. Dacay, Dulag and Brgy. 6, Tacloban City. The rationale behind the selection of two communities--one rural and one urban--was for comparative purposes. Brgy. Dacay, Dulag represented the former and Brgy. 6 the latter. The researchers conducted face-to-face interviews with 68 selected households at both barangays. In the study, energy consumption comprised household energy uses for various activities. Furthermore, energy consumption was estimated based upon electrical, LPG, fuelwood/charcoal, and kerosene consumption.
The study applied the multiple linear regression model to determine the effect of gender on household energy consumption behavior, among other variables. Research results revealed that the sex of the household head was a significant indicator of household energy consumption, among others. Furthermore, consistent with traditional gender roles, female heads and spouses of both communities were primarily engaged in household reproductive work, while males chiefly performed productive work. The incorporation of a gender dimension on energy consumption could be used as a basis for formulating energy interventions centered upon improving energy use and efficiency in the household level, especially benefitting women as they are primarily engaged in reproductive work.
Undergraduate thesis (B.A.S.S. Economics) -- University of the Philippines, Tacloban.